Effects Of Artemia Urmiana Enrichment In Larviculture Of Persian Sturgeon (Acipenser Persicus) Effects Of Artemia Urmiana Enrichment In Larviculture Of Persian Sturgeon (Acipenser Persicus) - Hafezieh, Mahmoud (2009)
The main objective of this study was to improve the Persian Sturgeon, Acipenser persicus survival when they released into the Caspian Sea through the enrichment of its larval food, Artemia urmiana. A series of experiments was conducted to evaluate effect several enrichment methods on the chemical composition of A. urmiana nauplii, larval growth, survival and salinity tolerance of the Persian sturgeon larvae. In the first series of 3 factorial experiment, the effects of oil sources, oil concentration and enrichment periods on the nutritive value of A. urmiana nauplii and growth rate, survival percentage, chemical composition and salinity tolerance of sturgeon larvae fed enriched Artemia and unenriched (as control) were evaluated. The results showed Total n-3 highly unsaturated fatty acid contents, DHA/EPA and ω3/ω6 ratios in Artemia nauplii and sturgeon larvae were significantly increased (P<0.05) as HUFA concentration and enrichment period increased. ICES30/4 with 300 ppm concentration during 24h enrichment period was the best combination treatment for improving the overall HUFA contents in Artemia (10.96±0.21 mg g-1 DW) and fish larvae (5.55±0.43 mg g-1 DW). Artemia enriched with HUFA oil did not affect the growth rate and survival percentage of larvae (P>0.05). When the sturgeon larvae were exposed to salinity test, those fed with HUFA enriched Artemia showed tolerance only up to 6 ppt. In the second series of 3 factorial experiment, the effects of oil sources each with 300 ppm concentration, ascorbyl palmitate levels and enrichment periods on the nutritive value of A. urmiana nauplii and growth rate, survival percentage, chemical composition and salinity tolerance of sturgeon larvae fed enriched Artemia and unenriched (as control) were evaluated. The results showed vitamin C contents were increased in both Artemia and fish larvae significantly (P<0.05). A 300 ppm ICES30/4 plus 20% AP with 24h enrichment period resulted in significantly higher (P<0.05) vitamin C content (1063.80± 48.00 μg/g DW) in Artemia nauplii in than any other combinations. The ICES30/4 supplemented with 10% AP during 24h enrichment period gave the highest vitamin C content in sturgeon larvae (175.21±7.43 μg/g DW). The growth rate of enriched sturgeon larvae were not increased significantly compared to control group (P>0.05). Survival rates and chemical compositions were significantly improved (P<0.05) in fish larvae fed Artemia enriched HUFA oil supplemented with AP. The ICES30/4 was the best oil source for improving the chemical composition including fatty acids in the larvae when it was supplemented with vitamin C. Lower levels of vitamin C (less than 30%) and longer enrichment period (24 h) were more effective (P<0.05) in improving the chemical composition of sturgeon fish larvae. When the sturgeon larvae were exposed to salinity test, those fed with HUFA +AP enriched Artemia demonstrated high tolerance (≥ 90% survival) up to 12 ppt for 120h. Although the enrichment of Artemia urmiana with 300 ppm ICES30/4 and 30% vitamin C gave the best salinity tolerance at 12ppt (100±0.00 % survival), the enrichment with 300 ppm sturgeon ovary oil and 10% vitamin C was economically affective in increasing the salinity tolerance of Persian sturgeon larvae (95±2.00 % survival).